Titrating haemophilia B phenotypes using siRNA strategy: evidence that antithrombotic activity is separated from bleeding liability - M. Metzger, Joseph; Tadin-Strapps, Marija; Thankappan, Anil; R. Strapps, Walter; DiPietro, Marti; Leander, Karen; Zhang, Zuo; K. Shin, Myung; Levorse, John; Desai, Kunal; Xu, Yiming; Lai, KehDih; Wu, Weizhen; Chen, Zhu; Cai, Tian-Quan; Jochnowitz, Nina; Bentley, Ross; Hoos, Lizbeth; Zhou, Yuchen; Sepp-Lorenzino, Laura; Seiffert, Dietmar; Andre, Patrick (Thrombosis and Haemostasis, 2015)
Haemophilia A and B are characterised by a life-long bleeding predisposition, and several lines of evidence suggest that risks of atherothrombotic events may also be reduced. Establishing a direct correlation between coagulation factor levels, thrombotic risks and bleeding propensity has long been hampered by an inability to selectively and specifically inhibit coagulation factor levels. Here, the exquisite selectivity of gene silencing combined with a gene knockout (KO) approach was used to define the relative contribution of factor IX (fIX) to thrombosis and primary haemostasis in the rat. Using a lipid nanoparticle (LNP) formulation, we successfully delivered fIX siRNAs to the liver by intravenous administration. The knockdown (KD) of target gene mRNA was achieved rapidly (within 24 hour post-siRNA dosing), sustained (maintained for at least 7 days post dosing) and not associated with changes in mRNA expression levels of other coagulation factors. We found that intermediate levels of liver fIX mRNA silencing (60–95 %) translating into a 50–99 % reduction of plasma fIX activity provided protection from thrombosis without prolonging the cuticle bleeding time. Over 99 % inhibition of fIX activity was required to observe increase in bleeding, a phenotype confirmed in fIX KO rats. These data provide substantial evidence of a participation of fIX in the mechanisms regulating thrombosis prior to those regulating primary haemostasis, therefore highlighting the potential of fIX as a therapeutic target. In addition, hepatic mRNA silencing using LNP-encapsulated siRNAs may represent a promising novel approach for the chronic treatment and prevention of coagulation-dependent thrombotic disorders in humans.
Keywords: siRNA; coagulation; factor fIX; thrombosis; haemostasis